Development of Automatic Fracture Detection System using Image Processing and Classification Methods for Femur Bone X-Ray Images - Deshmukh, MP; Deshmukh, PD (International Journal of Computer Sciences and Engineering, 2025)
Clinician and Practitioners suggest that detection of fractures from x-ray images is considered as an essential process in medical x- ray image analysis for diagnosis. Patients suffer in most cases seriously. So the study proposes a combined classification technique for automatic fracture detection from long bones, in particular the leg femur bones. The proposed system has following steps, preprocessing, segmentation, feature extraction and bone detection, which uses a combination of classification techniques of image processing for successful detection of fractures. The classifiers, Support Vector Machine Classifiers (SVM), feed forward Back Propagation Neural Networks (BPNN), and Naïve Bayes Classifiers (NB) are used during combination of classification. The results from various experiments showed that the proposed system is showing significant improvement in terms of detection rate of fractures.